Cadmium , nickel and lead in chocolates and candies from Baghdad markets in Iraq. - Samir Laybi Shkhaier (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2018)
Background:Foods and food  related products are imported  or  entered  to the country  by illegal ways , these foods may contain potential contaminants such as heavy metals . Among the most imported foods are chocolates and candieswhich consumed  frequently by children. Objective:In this study, selected heavy metals; Cadmium (Cd) , Nickel (Ni) and Lead (Pb)  were evaluated in commercial candies and chocolates products  that are commonly consumed by children in Iraq. The chocolates which studied were Twix (Germany) , Mars and Galaxy (Emirates)and the candies were Melody Pops (Iraq),  Caretos and Lip-Top (India) . Methods:Prospective study was done in Baghdad from January  to April 2017. 60 samples  of  three brands of chocolates and  threebrands of  candies (10 samples for each brand)  were analyzed  for their content of Cd , Ni and  Pb. Electrothermal Atomic Absorption Spectrometry (ETAAS) was used  for determination of metals under study . Results:Mean  levels of  Cd in three types of chocolates were  0.3282± 0.0203 µg/g in Twix chocolate , 0.323± 0.03199 µg/g  in Mars chocolate and  0.329± 0.01912µg/g in Galaxy chocolate  whereas  mean  levels of  Cd in three types of candies were  0.0947± 0.00386 µg/g  in Lip-Top candy , 0.093± 0.00368  µg/g in Melody – Pops candy and  0.0935± 0.003837 µg/g in Caretose candy,  while mean levels of  Ni in same  types of  chocolates were  4.38 ± 0.1109 µg/g , 4.23± 0.2111µg/g and  4.24± 0.2675µg/g    respectively  whereas  mean  levels of  Ni in same types of candies  were  1.417± 0.1µg/g  , 1.376± 0.05461 µg/g and  1.422 ±0.0968µg/g  respectively , in addition , mean levels of Pb in three types of chocolates were 2.212 ± 0.1398µg/g ,  2.185± 0.200 µg/g and  2.305± 0.2166 µg/g  respectively , whereas  mean  levels of Pb  in three types of candies were  1.17 ± 0.1149 µg/g  , 1.138± 0.08626µg/g  and 1.159±0.07156 µg/g  respectivelyConclusion:Contamination of chocolates and candies with these elements leads to health problems for citizens, especially children, and may lead to cancerous tumors. Therefore, children should be reduced to eating these foods. The government must strictly control the importation and entry of these foods